Measuring justice. (October 2019) - Cullerne Bown, William
The possibility of measuring the success of the criminal justice system in distinguishing the guilty from the innocent is often dismissed as impossible or at least impractical. Here I claim to demonstrate that such epistemic measurement would only be difficult. All measurement consists of two steps, the acquisition of observations and their processing through a computational framework. The law has lacked both, but I have recently put forward a computational framework and here I set out how the necessary observations can be obtained. This completes the conceptual foundations necessary for the development of jurisprudence as a social science, for policymaking in the law that is rooted in rational concern for epistemic outcomes, and for us to fulfil the modern, trustworthy and democratic promise that our forebears found in Blackstone's ratio.